2022
DOI: 10.1108/jstp-08-2021-0180
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant employees' attitudinal reactions to social distancing difficulties: a multi-wave study

Abstract: PurposeGrounded in the job demands–resources (JD-R) theory, this study investigates how the difficulty in social distancing at work, resulting from the COVID-19 crisis, may lead to intention to quit and career regret and how and when these effects may be attenuated.Design/methodology/approachThree-wave survey data were collected from 223 frontline service workers in a large restaurant company during the COVID-19 crisis.FindingsThe results show that difficulty in social distancing reduced employees' work engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…(2021) illuminated that in the era of the COVID-19 pandemic, customers are expected to do responsible shopping practices while service organizations are expected to engage primarily in essential service provision to avoid the spread of the COVID-19 pandemic. Similarly, Huo et al. (2022) found that service organization employees significantly suffer from social distancing measures in the era of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(2021) illuminated that in the era of the COVID-19 pandemic, customers are expected to do responsible shopping practices while service organizations are expected to engage primarily in essential service provision to avoid the spread of the COVID-19 pandemic. Similarly, Huo et al. (2022) found that service organization employees significantly suffer from social distancing measures in the era of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Mele et al (2021) illuminated that in the era of the COVID-19 pandemic, customers are expected to do responsible shopping practices while service organizations are expected to engage primarily in essential service provision to avoid the spread of the COVID-19 pandemic. Similarly, Huo et al (2022) found that service organization employees significantly suffer from social distancing measures in the era of the COVID-19 pandemic. Arguably, the impact of the COVID-19 pandemic will be also prevalent in the fitness service industry because the operation of personal training service necessitates an intense interaction between fitness service providers and customers.…”
Section: Jstp 331mentioning
confidence: 95%
“…The hospitality industry has been severely hit by the pandemic and stalled career opportunities (Huang et al, 2020), urging perceived employability in the external market imperative for hospitality workers (Huo et al, 2022). Perceived employability is related to one's perception of his or her prospects of obtaining and retaining employment (Berntson & Marklund, 2007; Vanhercke et al, 2014).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…, 2021), emotional labor (Zhan et al. , 2021) and turnover intentions and career regret (Huo et al. , 2022).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, we introduce FLE burnout due-to-customers , which we argue leads to many negative outcomes including, ultimately, FLEs leaving their job (Huo et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%